Golput dalam Perspektif Fiqh Siayasah (Studi Kasus Pemilihan Gubernur Jambi Tahun 2020) - Desri Kurniawan; Hermanto Harun; Hasbi Umar; Ramlah Ramlah; Novika wati (Dinasti Review, 2023)
The purpose of this research is to find out how the Fiqh Siyasah Perspective is towards people who do not choose their leaders, in the case study of the Jambi governor election in 2020. The type of research is field research, the research approach used is a qualitative approach using descriptive methods, the kind of data used is primary and secondary, and the data sources used are from people and sources. At the same time, the data collection methods are observation, interviews, and documentation. Based on the results of the research, it was concluded that there are still many abstentions, especially in the people of Jambi city, it was recorded that the level of cooperation of citizens in the political contestation in Jambi Pilkada last December 9, was only 67.90 percent occurred because the community did not know their position in the perspective of vinyasa fiqh based on the MUI fatwa when they don't choose their leaders, why do people choose to abstain from funds how to minimize people so they don't abstain.